Detection of collapsed buildings by classifying segmented lidar data: ISPRS Calgary Workshop, held on 29-31 August 2011, Calgary, Canada - Elberink, Sander Oude; Shoko, Moreblessings; Fathi, Seyed Abdolmajid; Rutzinger, Martin (2016)
https://www.researchgate.net/publication/264085078